Review of green building index in Malaysia; existing work and challenges - Algburi, Saleh M.; Abdul Aziz, Faieza; Baharudin, B.T. Hang Tuah (Research India Publications, 2016)
Energy is becoming one of the most critical and important aspect to the nation, countries with high percentage of energy and resources is considered powerful as nowadays energy and resources of the country is key measurement for its power and development. Economic improvement has now taken an imperative part in the current world as characteristic assets are a rare thing and accessible lodging area is decreasing with the blast of human population. Which increase the need of implementation of Green building construction to ensure sustainable development and reduce the consumption of resources. Green building is the act of building structures and utilizing procedures that are ecologically benevolent and asset productive all through a building's life-cycle from arrangement to outline, development, operation, upkeep, remodel and deconstruction. In Malaysia some world class Green Buildings have built in recent years, yet the idea of green buildings for general masses is in outset stage. During this paper, it will explore the overall of sustainable development with its concept and its importance of this approach and goals of green building. Advantages and elements of the assessment for Green building Index had been discussed with a number of the barriers to application and a review of existing mobile applications. In Malaysia, the dynamic development of practice development by the legislature, non-governmental associations and instruction, foundations in the recent years have demonstrated some empowering advance in this field as it had revealed in this paper.